Studies on enzyme action I : The correlation of the stereoisomeric α- and β-glucosides with the corresponding glucoses - Armstrong, Edward Frankland (1908)
Of the explanations put forward of the change in rotatory power which glucose undergoes in solution— a phenomenon discovered by Dubrunfaut in 1846— the most probable is that suggested by Lowry (Trans., 1899, 75, 213), which connects the change of rotatory power of glucose with a reversible isomeric change. When this explanation was first given, it was not possible to decide definitely what formulae were to be assigned to the dynamic isomerides. In view, however, of observations made during the investigation of various glucoside derivatives (Fischer and Armstrong, Ber., 1901, 34, 2885; 1902, 35, 833, 3144 and 3153), in the course of which the existence of two un doubtedly stereoisomerie series of glucose derivatives was discovered and their relationship to the α- and β-methylglucosides established, it now seems probable that a lactonic structure may be assigned to the isomeric glucoses: these isomerides are, in fact, the two possible stereoisomeric lactones.